Implementasi Kebijakan Publik pada Peraturan Daerah Nomor 10 Tahun 2014 tentang Kawasan tanpa Rokok di Rumah Sakit Umum Daerah Aloei Saboe Kota Gorontalo - Fidya Nur Alifah Mardjun; Asna Aneta; Fenti Prihatini (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to analyze the implementation of the Regional Regulation Number 10 of 2014 concerning Smoke-Free Areas (KTR) at Prof. Dr. H. Aloei Saboe Regional General Hospital in Gorontalo City based on Edward III's policy implementation theory, which includes the dimensions of communication, resources, disposition, and bureaucratic structure. The study used a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The results showed that the implementation of the KTR policy at Aloei Saboe Regional General Hospital has not been running optimally. In terms of communication, socialization and coordination have been carried out, but the delivery of information has not been effective, so there are still visitors who do not understand and comply with the rules. In terms of resources, budget support is considered sufficient, but there are still limitations in human resources, supporting facilities, and supervision. From the disposition aspect, implementers show an attitude of acceptance, support, and commitment to the policy, although the effectiveness of its implementation is still influenced by low public awareness and weak enforcement of regulations. Meanwhile, in terms of bureaucratic structure, the existence of Standard Operating Procedures (SOPs) has not been supported by adequate understanding from implementers, so its implementation has not been optimal. It was concluded that the implementation of the KTR policy at Aloei Saboe Regional Hospital has not been fully effective. Increased outreach, oversight, and commitment from all parties are needed to support the policy's success.